Penerapan Model Social Science Inquiry untuk Meningkatkan Kemampuan Berpikir Kritis - Ajeli, Fitri; Rizal, M. Syahrul; Fadhilaturrahmi, Fadhilaturrahmi; Yusnira, Yusnira; Aprinawati, Iis (MODELING: Jurnal Program Studi PGMI, 2023)
This study aims to improve the critical thinking skills of fourth grade students of SDN 002 Langgini in the 2022/2023 school year, totaling 26 students. Critical thinking is an active consideration that is continuous and thorough about a belief or form of knowledge that is taken for granted by including supporting reasons and rational conclusions. This research method is Classroom Action Research (PTK) which is carried out in 2 learning cycles. Each cycle consists of 2 meetings and 4 stages of learning, namely: planning, implementation, observation and reflection. The research time was carried out in May 2023. Data collection techniques in the form of documentation, observation and tests. The results of critical thinking skills of grade IV students of SDN 002 Langgini in cycle 1 meeting 1 with a percentage of learning completeness of 35% and in cycle 1 meeting 2 increased with a percentage of learning completeness of 46%. In cycle 2 meeting 1 also increased with a percentage of 61% learning completeness and in cycle 2 meeting 2 increased again with a percentage of 84% learning completeness. Thus it can be concluded that the application of the Social Science Inquiry learning model can improve the critical thinking skills of fourth grade students of SDN 002 langgini.